2020
DOI: 10.3389/fpsyg.2020.00880
|View full text |Cite
|
Sign up to set email alerts
|

Visual Search in Chinese Children With Attention Deficit/Hyperactivity Disorder and Comorbid Developmental Dyslexia: Evidence for Pathogenesis From Eye Movements

Abstract: In this study, a visual search task was conducted on children with comorbid attention deficit/hyperactivity disorder (ADHD) and developmental dyslexia (DD), children with pure ADHD, and typically developing children to explore the pathogenesis of comorbidity between ADHD and DD. Participants searched for the target character from five characters in each trial during the task. The distractors included orthographically similar characters, homophones, unrelated characters, and characters of a different color (i.e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 40 publications
1
8
0
1
Order By: Relevance
“…Noteworthy, and differently from SCZ, fixation duration paralleled typical duration of search and scanning time, suggesting that ADHD might have had more cognitive resources than SCZ to perform the task efficiently, while opting for a focal search strategy, like SCZ. Only two other studies have assessed VS in children with ADHD including fixation-related measures [ 48 , 63 ]. Cui et al [ 63 ] found prolonged first fixation duration but typical gaze duration (as the sum of all fixation durations), which resembles the finding of typical search duration found here, leading to atypical search processing limited to an early stage of search in ADHD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Noteworthy, and differently from SCZ, fixation duration paralleled typical duration of search and scanning time, suggesting that ADHD might have had more cognitive resources than SCZ to perform the task efficiently, while opting for a focal search strategy, like SCZ. Only two other studies have assessed VS in children with ADHD including fixation-related measures [ 48 , 63 ]. Cui et al [ 63 ] found prolonged first fixation duration but typical gaze duration (as the sum of all fixation durations), which resembles the finding of typical search duration found here, leading to atypical search processing limited to an early stage of search in ADHD.…”
Section: Discussionmentioning
confidence: 99%
“…Only two other studies have assessed VS in children with ADHD including fixation-related measures [ 48 , 63 ]. Cui et al [ 63 ] found prolonged first fixation duration but typical gaze duration (as the sum of all fixation durations), which resembles the finding of typical search duration found here, leading to atypical search processing limited to an early stage of search in ADHD. In contrast to the present finding, Seernani et al [ 47 ] reported typical average fixation duration per trial in the ADHD group.…”
Section: Discussionmentioning
confidence: 99%
“…Each of our cases revealed specific symptoms of dyslexia. Case D1 has deficits of reading skills, which is probably related to ADHD [15]. Also, both of D2 and D3 are more energetic in the evening than in the daytime, in addition to reading and writing impairments.…”
Section: Resultsmentioning
confidence: 99%
“…Dyslexia may happen together with autism [14] and/or attention deficit hyperactivity disorder (ADHD) [15]. The proband has normal intelligence but seems to be a spectrum with different severities [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation